2018
DOI: 10.3389/fneur.2018.00211
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographical Gait Characteristics in Parkinson’s Disease: Effects of Combined Physical Therapy and Rhythmic Auditory Stimulation

Abstract: BackgroundIn persons with Parkinson’s disease (PD), gait dysfunctions are often associated with abnormal neuromuscular function. Physical therapy combined with auditory stimulation has been recently shown to improve motor function and gait kinematic patterns; however, the underlying neuromuscular control patterns leading to this improvement have never been identified.Objectives(1) Assess the relationships between motor dysfunction and lower limb muscle activity during gait in persons with PD; (2) Quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Beckelhimer et al (2011) showed improved upper-limb functionality in two participants who had suffered stroke, and Johansson et al (2012, 2014) saw improved upper-limb movement in two different case studies of children with a different severity of cerebral palsy. An extensive number of clinical studies have also shown that fixed-tempo by the use of Rhythmic Auditory Stimulation (RAS) improves different aspects of gait timing (e.g., Thaut et al, 1996; Hove et al, 2012), and have described the effectiveness of RAS and its promising therapeutic role of improving different aspects of gait performance in patients affected by Parkinson’s disease (e.g., Thaut and Abiru, 2010; Murgia et al, 2015, 2018; Pau et al, 2016; Dalla Bella et al, 2017; Bailey et al, 2018). It’s suggested that RAS would facilitate the activity of the internal clock, thus dys-functioning in patients with Parkinson’s disease (PD), and thereby help in regulating the fluidity of muscular activation, improving coordination, and facilitating the execution of automatic movements, such as walking in PD (Murgia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beckelhimer et al (2011) showed improved upper-limb functionality in two participants who had suffered stroke, and Johansson et al (2012, 2014) saw improved upper-limb movement in two different case studies of children with a different severity of cerebral palsy. An extensive number of clinical studies have also shown that fixed-tempo by the use of Rhythmic Auditory Stimulation (RAS) improves different aspects of gait timing (e.g., Thaut et al, 1996; Hove et al, 2012), and have described the effectiveness of RAS and its promising therapeutic role of improving different aspects of gait performance in patients affected by Parkinson’s disease (e.g., Thaut and Abiru, 2010; Murgia et al, 2015, 2018; Pau et al, 2016; Dalla Bella et al, 2017; Bailey et al, 2018). It’s suggested that RAS would facilitate the activity of the internal clock, thus dys-functioning in patients with Parkinson’s disease (PD), and thereby help in regulating the fluidity of muscular activation, improving coordination, and facilitating the execution of automatic movements, such as walking in PD (Murgia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This type of filter removes the high-frequency components and smoothens the data thus enhancing the quality. Under low pass filter, Butterworth filter (BF) is the frequently used filter and have the unique property of flat frequency response in the passband area [70], [71]. BW filter resolves the problem of blurred edges which is often encountered in an ideal low pass filter.…”
Section: ) Filteringmentioning
confidence: 99%
“…The analysis revealed more postural deflects in PD with FOG subjects as compared to others and high relevance of COP than COP in PD inspection. Another study by Bailey et al [70] explored frequency and time domain features (RMS, modulation index, covariance, asymmetry index, etc.) to test the reliability of PT-RAS therapy in reducing asymmetry in PD patients.…”
Section: ) Kinetic Featuresmentioning
confidence: 99%
“…A comprehensive literature of EMG applications to clinical purposes can be found, spanning through a variety of investigated muscles and pathologies, in order to detect abnormal patterns with evaluation, diagnosis, and rehabilitation aims. We report on a subset of paradigmatic applications that include, but are not limited to, the assessment of lower-back pain [15,16]; the investigation of patterns for motor recruitment [17]; the analysis of walking patterns in Parkinson's [18]; gait pattern abnormality detection in multiple sclerosis [19]; applications to stroke hand rehabilitation [20]; and many others.…”
Section: Introductionmentioning
confidence: 99%